Contextualization Of Multicultural Values On Education In Qs. Al-Hujurat Verses 10-13 Perspective Of Ibnu Katsir's Interpretation - Asep Supriyadi; Abdul Basir; Siti Aisyah (Pasundan Social Science Development, 2026)
Indonesia is characterized by a rich mix of ethnic groups, cultures, languages, and religions, making it essential to promote multicultural values ??to ensure unity among its people. Nonetheless, issues such as intolerance, discrimination, hate speech, and conflicts related to ethnicity, religion, race, and inter-group relations frequently arise, often fueled by social media platforms. The verses 10 to 13 of QS. Al-Hujurat conveys teachings about brotherhood, mutual respect, equality, and the need to shun discrimination. Ibn Kathir's interpretation highlights that true human worth is determined by one's piety rather than ethnic background or social rank. This study seeks to contextualize the multicultural principles present in these verses, aiming for their implementation in educational settings to cultivate a peaceful, respectful, and harmonious learning environment. The research uses a qualitative approach, specifically through library research. The sources of data include Tafsir al-Qur'an al-'Azim by Ibn Kathir, the Qur'an itself, and pertinent literature addressing multiculturalism. The results show that the multicultural values ??recognized include tolerance, equality, justice, democracy, and fraternity. By integrating these values ??into education, it is possible to enhance unity and create a harmonious learning environment amid the existing diversity.